IMPLEMENTASI BANTUAN PANGAN NON TUNAI KOTA SEMARANG TAHUN 2019 - Saputra, Muhammad Aldi Nur; Harsasto, Priyatno - (Journal of Politic and Government Studies, 2020)
This research is motivated by the many policies issued by the Government to alleviate poverty, one of which is the Non-Cash Food Assistance program. However, seeing the phenomena that occur in the distribution of this program, there are several obstacles, one of which is the inaccurate target, there are still many people who are able to receive assistance, while those who are truly unable are not recorded in the recipients of this program assistance. Then there was the delay in making KKS for KPM, and there were still people who could not withdraw BPNT there were also those whose balance on the KPM card was zero than what it should have been Rp. 110,000, - per month and there are recipients who are recorded but only received one aid and never received any more assistance. This study aims to determine how the implementation of the NonCash Food Assistance Program (BPNT) policy in North Semarang District as the largest recipient of assistance and Tugu District as the lowest aid recipient. The theory used in this research is George C. Edwards III theory. There are four dimensions that influence the success of Policy Implementation, namely Communication, Resources, Implementing Disposition, Bureaucratic Structure. The research method uses qualitative methods with a descriptive approach, the types of data used are primary and secondary data. Data collection techniques through interviews, observation and documentation study. The informants in this study were the Head of Social Welfare Section of Tugu and North Semarang Subdistricts, the District Coordination Team, the owner of the e-warong agent, the Recipient Community. Research Results The Implementation of BPNT Program Policies in Semarang City, especially North Semarang District has not been implemented optimally. This shows that there are several factors that are still experiencing problems. There are significant obstacles or problems, namely there are still people who feel that this assistance is deemed insufficient to meet the basic needs of the household, there are still inaccurate BPNT recipients, lack of socialization resulting in a lack of public understanding, and delays in making KKS KPM cards and delays in rice distribution due to the large number of KPM in North Semarang District. The conclusion of this research is that at the point of communication, the implementation still needs to be improved again because factors that are found to be obstacles between program implementers and program targets have found a gap where not all people know BPNT and just accept the lack of public awareness to realize this program is indeed targeted. -True for people who cannot afford and have not received food assistance, so as not to cause targets that are not on target. at the point of implementing resources from human resources as implementers of the BPNT program, human resources who provide services are responsive enough in handling complaints and friendly when handling related questions about BPNT so as to provide comfort and convenience for the community, but in terms of budget implementation still needs to be reviewed again due to the increase in food prices which the government did not anticipate in terms of disposition, looking at the characteristics of policy administrators who have good honesty and commitment, this is evidenced by the parties who have tried to work together to provide information about the BPNT program to the public. In the implementation of the mechanism, from registration to medical services, it has been carried out quite well, it is proven that the KPM received a letter from the kelurahan delivered by the local RT / RW for KPM participation in BPNT. Then the KPM was directed to the kelurahan to include the KK and KTP of the head of the family which were considered quite easy